DDT and endrin residues in cotton seeds, oils and meals - Novo, José Poleze Soares; Batista, Gilberto Casadei de; Lima, Urgel de Almeida; Cia, Edivaldo (Pesquisa Agropecuaria Brasileira, 2014)
Residues of DOT and endrin in cotton seeds (Gossypium hirsutum L., cultivar IAC-17), oils and meals were determined by gas chromatography in the State of São Paulo, Brazil. Spraying applications were made at 76, 56 and 31 days before harvest at the following dosages: 2000 g a.i./ha DDT and 8009 a.i./haendrin, applied as a wettable powder formulation for DDT and as an emulsifiable concentrate for endrin. The persistence of both insecticides in cotton seeds was similar, considering the amount applied and the final residues, which were 0.099 ppm of total DDT residues (sum of p,p'-DDE, o,p'-DDT and p,p'-DDT) and 0.04 ppm of endrin residues. The crude oil has showed higher residue levels: 0.181 ppm and 0.083 ppm for total DDT and endrin, respectively. The meals have showed lower residue levels: 0.025 ppm of total DDT and 0.01 ppm of endrin. The residue levels found in cotton seeds were in accordance with the official tolerances, which are 1.0 ppm for total DDT residues and 0.1 ppm for endrin residues, with a safety interval of 30 days.